2016
DOI: 10.1186/s13561-016-0102-x
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance subscription among women in reproductive age in Ghana: do socio-demographics matter?

Abstract: BackgroundPremised that health insurance schemes in Africa have only been introduced recently and continue evolving, various concerns have been raised regarding their effectiveness in improving utilisation of orthodox health care and the reduction of out-of-pocket expenditures for their population, particularly women.ObjectiveTo examine the effects of socio-demographics on health insurance subscription among women in Ghana.MethodsThe study draws on the 2014 Ghana Demographic and Health Survey. Bivariate descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
57
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 19 publications
9
57
1
2
Order By: Relevance
“…Thus, it was realised that the probability of giving birth at a health facility increased by education, not only for the women but also for their partners. These findings are thus in congruence with previous studies which found education as a strong determinant of health care service and facility use [23, 2830]. The fact that partner's education predicted the choice of place of delivery among the women, however, supports the argument that men usually control decision-making in the home, including women's health decision-making [31, 32].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, it was realised that the probability of giving birth at a health facility increased by education, not only for the women but also for their partners. These findings are thus in congruence with previous studies which found education as a strong determinant of health care service and facility use [23, 2830]. The fact that partner's education predicted the choice of place of delivery among the women, however, supports the argument that men usually control decision-making in the home, including women's health decision-making [31, 32].…”
Section: Discussionsupporting
confidence: 90%
“…This points to long distances that are usually travelled by rural women in order to access maternal health care as found in previous studies [23, 27]. Roads in these rural areas are also mainly in a deplorable state [33, 34].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our findings are similar to those of Jean et al [9] in Douala-Cameroon, where lack of awareness and limited knowledge on the basic concepts of CBHI, and high premiums were reasons for low insurance enrollment. Amuh A. H et al [16] in Ghana found that the major barriers to health insurance subscription included; long queues and waiting time, and negative attitude of service providers both at the healthcare facilities and the health insurance office.…”
Section: Discussionmentioning
confidence: 99%
“…These ascriptions normally make male partners the heads of their respective households. As heads of households, the males mainly decide the means of healthcare accessibility including where the women should seek care [39]. Male partner involvement refers to "the various ways in which men relate to reproductive health problems and programmes, reproductive rights, and reproductive behavior" [40].…”
Section: Discussionmentioning
confidence: 99%